Presenteeism and burnout among teachers in public and private Portuguese elementary schools - Ferreira, A. I. (2017)
This research aims to study the possible relation between presenteeism and burnout in the public and private education sector. Presenteeism - a groundbreaking concept in organizational behaviour literature - refers to productivity losses that occur when employees come to work but under-perform due to physical and psychological causes. Next, we further clarified the burnout criterion with three groups of predictors: personal, contextual and presenteeism. Results from a sample of 281 elementary school teachers from private and public institutions revealed that personal and contextual characteristics as well as presenteeism were predictive of teacher burnout. We also found that public school teachers exhibited higher levels of both presenteeism and burnout. Finally, the implications of these results are discussed and directions for future research in the field are provided.